Pengaruh Jumlah Aktiva Tetap, Hutang Jangka Panjang, dan Modal terhadap Kinerja Keuangan LPD Pakraman Tajen, Kecamatan Penebel, Kabupaten Tabanan, Bali - NI KADEK ANISA DWI PURNANTARI; I NYOMAN GEDE USTRIYANA; A.A.A. WULANDIRA SAWITRI DJELANTIK (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
The Influence of Total Fixed Assets, Long-Term Debt, and Capital on The Financial Perfomance of LPD Pakraman Tajen, Penebel District, Tabanan Regency, Bali The lack of capacity of village credit institutions (LPD) in utilizing all potential resources to improve operational activities will have an impact on the ability to earn income and its overall financial performance. Factors that support operational activities of an LPD include fixed assets, long-term debt, and capital. This study aims to examine the effect of fixed assets, long-term debt, and capital on financial performance. This research was conducted at LPD Pakraman Tajen, and the data was obtained through field research which was then analyzed using descriptive methods and multiple linear regression. This study shows that the total fixed assets, long-term debt, and capital significantly affect financial performance. The number of fixed assets, long-term debt, and capital partially have a signifivant effect on financial performance.